Hemichorea-hemiballismus in a patient with hyperglycaemic hyperosmolar state - Reng, Rifkatu S.; Kenechukwu, Odumodu; Ramatu, Shuaibu; Shyngle, Oyakhire; Special, Omonua; Ogugua, Osi-ogbu; Anumah, Felicia (International Journal of Research in Medical Sciences, 2020)
Hemichorea-hemiballismus (HCHB) is a rare manifestation of hyperglycaemic hyperosmolar state caused by contralateral lesion in basal ganglia. A 74-year-old, known diabetic and hypertensive woman presented with one-week history of high-grade fever and loss of consciousness associated with involuntary movement of the right upper and lower limbs for 10 hours prior to presentation. Physical examination revealed pyrexia, tachycardia and altered sensorium. Blood glucose was 53.8 mmol/l, hemoglobin A1c (Hb A1c) 9.9% and brain computed tomography (CT) scan showed cerebral atrophy with bilateral basal ganglia hyperdensities. Escherichia coli was cultured from the urine. She did well on treatment with soluble insulin, rehydration and intravenous ceftriaxone. HCHB is a rare complication seen in patients with poorly controlled diabetes mellitus. This report highlights the reversibility of the disease with prompt diagnosis and appropriate insulin treatment. HCHB should be distinguished from other intracranial pathologies.